Online Loan Services in the Perspective of Islamic Law: Analysis of the Ijtima' Ulama Decision of the Indonesian Fatwa Commission VII of 2021 Regarding Online Loans - Muhammad Nazar Nazar; Sitti Zahra Aulia Nazar (Journal of Law, Social Science and Management, 2025)
Background: The increasing needs after the Covid-19 pandemic are often constrained by financial aspects. The ease of using money lending services, both conventionally and internet-based such as online loans, is an option that is quite profitable for the community on the one hand. However, on the other hand, online loans can cause losses.. Objective: The purpose of this study is to comprehensively discuss online loan services from an Islamic law perspective based on an analysis of the decision of the ijtima' ulama of the Indonesian fatwa commission VII in 2021 regarding online loans Methods: This article is a descriptive study that describes the existing facts. Other information is obtained from various verses of the Koran, Hadith, books, journals and other literature. Results: The results of the study show that debt based on the results of the decision of the ijtima' ulama of the Indonesian fatwa commission VII in 2021 is something that is recommended based on the principle of mutual assistance without an interest system, however, if in the implementation of the online loan service there is an element of usury, it is forbidden to do it, so it is better to abandon it. Therefore, it is necessary to find other alternatives by avoiding everything that has harmful value. Conclusion: Based on the ijtima'ulama decision of the VII fatwa commission throughout Indonesia in 2021 regarding online loans, several important matters were discussed: 1) tabarru contracts, 2) delaying payment times, making threats, giving an interest system is something that is forbidden. Therefore, the urgency regarding online loans should be avoided with good intentions and with great care. This is by considering the elements of mudharat which are likely to be more than maslahah. Keywords: Online Loans; Scholars; Islamic Law; Indonesia